2013
DOI: 10.1063/1.4825222
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study on the impact of heavy doping on Si intrinsic point defect properties and implications for single crystal growth from a melt

Abstract: Density functional theory (DFT) calculations are performed to obtain the formation energies of the vacancy V and the self-interstitial I at all sites within a sphere around the dopant atom with 6 Å radius for V and 5 Å radius for I in Si crystals. Substitutional p-type (B and Ga), neutral (C, Ge, and Sn), and n-type (P, As, Sb, and Bi) dopants were considered. The results show that the formation energies of V and I around dopant atoms change depending on the types and sizes of the dopants, i.e., depending on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 46 publications
8
55
0
Order By: Relevance
“…On the other hand, K. Sueoka et al have derived the bond lengths of Si-P and Si-As to be 2.306 and 2.473 Å, respectively, based on the DFT calculations. 12 Such result supports that the Si-P bond has a larger bonding energy than the Si-As one.…”
Section: A Bonding Energies Of Si-as and Si-p Bonds In Siliconsupporting
confidence: 75%
See 2 more Smart Citations
“…On the other hand, K. Sueoka et al have derived the bond lengths of Si-P and Si-As to be 2.306 and 2.473 Å, respectively, based on the DFT calculations. 12 Such result supports that the Si-P bond has a larger bonding energy than the Si-As one.…”
Section: A Bonding Energies Of Si-as and Si-p Bonds In Siliconsupporting
confidence: 75%
“…Note that the lattice strain introduced by As-doping is negligible (0.001 × C D ) while that resulted from P-doping is relatively remarkable (-0.091 × C D ), where C D refers to the dopant concentrations. 12 Moreover, the Si-P bond length (2.306 Å) is smaller than the Si-As one (2.473 Å). 12 Such difference in the doping effects of P and As will probably lead to somewhat different mechanical properties of heavily P-and As-doped CZ-Si wafers, which is an intriguing subject to be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen, the vacancy configuration is more and more energetically stable as the vacancy progressively approaches the Ge atom, suggesting that the vacancy tends to locate at the first nearest neighboring (1NN) sites of the Ge atom. Actually, it has been previously reported that the vacancy formation energy at 1NN sites of the Ge atom is the lowest [42][43][44], in consistent with the present result. It is reasonable that during the high temperature RTP the formation of vacancies at the 1NN sites of the Ge atoms is beneficial for relieving the stress due to the oversize Ge atoms in Si 1-x Ge x .…”
Section: Oxygen Diffusion In Cz-si 12x Ge X and Cz-sisupporting
confidence: 94%
“…In another study, 21 it was shown that most of the reported experimental results on intrinsic point defect behavior in heavily doped Si can be explained on the basis of Voronkov model when taking into account that (1) the incorporated total V and I concentrations at melting point depend on the types and concentrations of dopants, and that (2) most of the total V and I concentrations during Si crystal growth contribute to the intrinsic point defect pair recombination at temperatures much higher than those to form grown-in defects. Further theoretical and experimental studies to couple the impacts of thermal stresses and dopant atoms are needed to explain and engineer the intrinsic point defect behavior in single crystal Si growing from a melt using a unified model valid for all pulling processes, crystal resistivities and not electrically active impurity concentrations.…”
mentioning
confidence: 98%